2014
DOI: 10.1590/s1516-14392014005000063
|View full text |Cite
|
Sign up to set email alerts
|

Surface contact fatigue failure of a case hardened pinion shaft

Abstract: An investigation was made to determine the causes of surface contact fatigue failure of a case hardened driver pinion located in the intermediate shaft of a reducer gearbox used in a sugar and alcohol mill. The examination of the component revealed the presence of a cemented layer substantially thicker than that generally specified for pinions devised for this application. This, associated with the massive presence of brittle threadlike carbon-rich cementite phase (Fe 3 C) in prior austenite grain boundaries o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 8 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…Lee et al (2006) further reported that treatment temperatures between 870 o C and 860 o C minimized residual stress without substantially compromising the hardness of the treated case. Stress corrosion cracking, brittle fracture, fatigue failures are main associated failures while carrying out the flame hardening (Rossino et al,2014) due to improper selection and control of thermal process parameters. Grum et al (2001) focused on increasing the hardness by mechanized flame hardening procedure though, the optimal process parameters were not considered.…”
Section: Flame Hardeningmentioning
confidence: 99%
“…Lee et al (2006) further reported that treatment temperatures between 870 o C and 860 o C minimized residual stress without substantially compromising the hardness of the treated case. Stress corrosion cracking, brittle fracture, fatigue failures are main associated failures while carrying out the flame hardening (Rossino et al,2014) due to improper selection and control of thermal process parameters. Grum et al (2001) focused on increasing the hardness by mechanized flame hardening procedure though, the optimal process parameters were not considered.…”
Section: Flame Hardeningmentioning
confidence: 99%